THE EFFECT OF EARNINGS PER SHARE, RETURN ON EQUITY, AND DEBT TO EQUITY ON BUMN COMPANIES - Mega Citra Tumorang; Ike Rukmana Sari; Ribka Ribka (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
What we do in this research is to find out the influence, investigate, and get an understanding or understanding of whether Earning Per Share, Return On Equity, and Debt To Equity together or individually have an effect on Stock Prices in State-Owned Enterprises for the period 2018-2018. 2020. Quantitative approach is an approach used in our research. The type of research that we use for research is descriptive research, because it is based on the quantity and analysis of data obtained from statistical data processing. Linear Regression Analysis is a method or technique used by researchers to examine the results of our research. There are 50 population of State-Owned Enterprises in 2018-2020 with a sample of 60 State-Owned Enterprises for the period 2018-2020. The variables in this study also affect the independent variables, on the other hand, partially EPS and ROE have no effect on stock prices in State-Owned Enterprises for the 2018-2020 period, while the DER variable has a negative and significant effect on prices. shares of State-Owned Enterprises for the period 2018-2020. From the research that we have done, we can conclude that the result of the coefficient of determination R-Squared (R2) is 0.084 or a value of 8.4% and the remaining 91.6% does not include the variables in this study